Borys Hrinchenko in the memories of contemporaries - Ivashchenko, Mariia (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2024)
The article analyzes the reception of B. Hrinchenko's work in criticism, elaborates studies of his contemporaries, devoted to his biography, social and literary activities. The main attention is focused on the aspect of the artist's writing work, the prerequisites for its formation, as well as the author's inherent character traits and features of appearance, which testified to the writer's strong-willed qualities and contributed to his searches. He reacted acutely to the injustice and injustice inflicted on the Ukrainian people, in particular by the numerous bans on the Ukrainian language, and was concerned with national and social issues at a time when inequality and the poor were chaining the impoverished people into chains of obedience and submission. The writer saw not the only salvation in enlightenment, the instrument of which became the embodiment of literature.The object of the study was the autobiography of B. Hrinchenko, the memoirs of M. Hrinchenko, I. Lypa, M. Lysenko, D. Pisochnytsia, the works of S. Yefremov "Borys Hrinchenko (About his life and works), M. Plevako's "Life and work of Borys Hrinchenko", "Cedar of Lebanon" by M. Chernyavskyi, criticism by L. Smilyanskyi, S. Rudnychenko, V. Koryak. The literary works of O. Biletsky, N. Kobyzhcha, A. Movchun, O. Nezhivy, A. Pogribny, and others were analyzed.The purpose of this article is to form a holistic and objective view of B. Hrinchenko's life, literary activity, character, moral values and orientations with the help of reviews of contemporaries who accompanied the writer on various aspects of his life and professional path. The topicality of the topic is due to the fact that B. Hrinchenko's work becomes the object of research by literary critics much less often than works devoted to pedagogical and educational views, scientists reveal ideological-aesthetic and national-social aspects, carrying out a detailed analysis of biography, epistolary, journalism, ethnographic works. Despite the limited amount of critical literature, the chosen topic is promising and needs more detailed coverage.